Controller project: computational modeling of an intraesophageal device for reducing the risk of atrioesophageal fistula during cardiac radiofrequency ablation - Barreto Mota da Costa, Lindemberg; Fleury Rosa, M´ario Fabr´ıcio; Almeida da Silva, Ana Karoline; Mendes Faria, Rafael; Marcelino de Almeida Nunes, Gustavo Adolfo; Campos de Oliveira, Gabriela; Soares, Breno Hugo; Barbosa Fernandes, Bruna; Duarte Domínguez, Aldira Guimarães; Ferreira da Rocha , Adson; et al. (Revista Interdisciplinar de Pesquisa em Engenharia, 2025)
Abstract: Background: Cardiac radiofrequency (RF) ablation is widely used to treat arrhythmias, but it carries the risk of thermal injury to the esophagus, potentially leading to atrioesophageal fistulas—a severe and often fatal complication. This study aimed to develop and evaluate an intraesophageal controller device to mitigate these thermal effects. Methods: A computational model based on the finite element method (FEM) was developed using COMSOL Multiphysics 6.0 to simulate thermal dissipation during RF ablation. The 3D geometry included the left atrium, esophagus, periesophageal adipose tissue, and RF source. Three thermal mitigation strategies were tested: active cooling, thermal insulation, and contact modulation. RF power levels of 30 W, 40 W, and 50 W were also analyzed. Experimental validation was conducted with biomimetic models. Results: Without thermal control, esophageal temperatures reached 52°C within 30 seconds. Active cooling reduced this to 38.5°C, thermal insulation to 41°C, and contact modulation yielded average reductions of 6°C depending on position. At 50 W, only active cooling kept temperatures below critical thresholds. Experimental results closely aligned with simulations, showing temperature deviations under 2°C. Conclusions: The intraesophageal controller with active cooling proved most effective, reducing esophageal temperature by 27%, compared to 21% with thermal insulation and 12% with contact modulation. Computational modeling was essential for optimizing design and evaluating efficacy. Future studies should focus on in vivo validation to confirm safety and clinical viability.